Alternative feed resources in the era of climate change: A review - Ojediran, Taiwo K; Olofintuyi, Olajide S; Ojediran, Temitope J (Aceh Journal of Animal Science, 2024)
Climate change poses significant challenges to traditional feed resources, impacting livestock production and food security. In response, the search for alternative feed resources has gained momentum, aiming to enhance the resilience and sustainability of agriculture in a changing climate. This review explores a diverse array of alternative feed resources that show promise in mitigating the impacts of climate change on feed availability and quality.Drawing froma comprehensive analysis of industry reports, case studies, and articles from sources such as Elsevier, Scopus, PubMed, ScholarOne, PLUS One, Science Direct, and Google Scholar, thisstudy covers a range of innovative options, including insect-based feeds, algae, seaweeds, microbial proteins, residues, by-products, aquatic plants and weeds, hydroponic fodder production, climate-resilient forage crops, agroforestry systems, high-value crop by-products, and silvopastoral systems. Each alternative feed resource is examined in terms of its nutritional value, environmental benefits, and potential challenges to adoption. The review underscores the importance of developing and implementing climate-resilient livestock feeding strategies to ensure food security and sustainability in a changing climate. In light of climate change, this study explores the effects of switching to other feed sources in livestockproduction. Further research and policy support are emphasized to facilitate the integration of these alternative feed resources into livestock production systems worldwide. By embracing these innovative approaches, the agricultural sector can build resilience, reduce environmental impacts, and secure food supplies amidst climate change challenges through insect-based feeds, hydroponic fodders, agro-industrial byproducts, aquatic plants and algae, among others can be used as substitutes in the era of climate change